My second first year : leaving academia for a high school classroom - Jones, Joseph R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
"Dr. Jones returned to the high school classroom after 15 years in higher education, most recently as an Associate Dean. This text chronicles his journey into his new teaching career. The premise of the text is framed on the attributes of a relational pedagogy. As such, the book discusses the relationships that Dr. Jones developed throughout the academic year. In this capacity, relational pedagogy allows the reader a unique lens through which to view the schooling process in this metropolitan southern town. In the book, Jones examines topics such as standardized testing, racism, sexuality, cheating, among other topics, through a critical theory paradigm. In doing so, Jones is able to interweave theoretical concepts within the daily actions of the schooling process. As such, the text is a unique reconceptualization of schools and the purpose of schools"--